Despesas de investimento municipais das capitais brasileiras no período 2001-2008: O que podemos inferir com base nos dados bimestrais dos relatórios resumidos de execuç\~ao orçamentária? - Márcio Bruno Ribeiro; Alessandra dos Santos Ferreira; Hilton Leal Silva; Wanderson Silva Rocha (Instituto de Pesquisa Econômica Aplicada (IPEA), 2010)
– This paper attempts to discuss quality and some improvements in high frequency time series data of the nominal gross investment expenses for Brazilian municipalities which are state capitals. We first utilized data for the 2001-2008 period available in Relatórios Resumidos de Execuç\~ao Orçamentária, a bi-monthly public accounts report published by the Brazilian federal, state and local governments according to the directives of Fiscal Responsibility Law (LRF). Then, we evaluate the consistency of this information and propose some adjustments to improve data quality. Finally, we present resultant time series and give a brief analysis about its properties during that period.
Keywords: C82; E62; H72; 330; Öffentliche Investition; Kommunale Ausgaben; Zeitreihenanalyse; Brasilien